2019
DOI: 10.1136/bmjopen-2019-031352
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations of psychosocial work exposures with mortality in France: STRESSJEM study protocol

Abstract: IntroductionAlthough evidence has been provided on the associations between psychosocial work exposures and morbidity outcomes in the literature, knowledge appears much more sparse on mortality outcomes. The objective of STRESSJEM is to explore the prospective associations between psychosocial work exposures and mortality outcomes among the national French working population. In this paper, we describe the study protocol, study population, data sources, method for exposure assessment, data analysis and future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The proportions were the following for smoking-related mortality, 25.6% (29.7% for men, 13.1% for women), alcoholrelated mortality, 5.4% (5.7% for men, 4.3% for women), and external causes of death, 12.7% (13.5% for men, 10.5% for women). A description of psychosocial work exposures among the study sample is presented in our study protocol (Niedhammer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportions were the following for smoking-related mortality, 25.6% (29.7% for men, 13.1% for women), alcoholrelated mortality, 5.4% (5.7% for men, 4.3% for women), and external causes of death, 12.7% (13.5% for men, 10.5% for women). A description of psychosocial work exposures among the study sample is presented in our study protocol (Niedhammer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The details of the protocol and methods of the STRESSJEM study can be found in a previous publication (Niedhammer et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…There were 13.6 million and 11.6 million person-years in the follow-up period for men and women, respectively. The mean duration of follow-up was 17 years for both genders ( 21 ). Over 1976–2002, there were 19 264 cardiovascular deaths (14.19 cases per 10 000 person-years) among men and 6181 (5.35 per 10 000 person-years) among women, including 2988 cardiovascular deaths (2.89 per 10 000 person-years) among men and 474 (0.56 per 10 000 person-years) among women during time intervals with a job (on-the-job cardiovascular mortality).…”
Section: Resultsmentioning
confidence: 99%
“…All details about person-years, number of cases, and cases per 10 000 person-years for cardiovascular, IHD and stroke mortality are provided in supplementary table S1. The description of exposures was presented in our study protocol ( 21 ). Women had a higher prevalence of exposure to high psychological demands, low decision latitude, low social support, job strain, and iso-strain than men.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the STRESSJEM study protocol are presented in a previous publication [5] and in the online supplementary material (for all online suppl. material, see www.karger.com/doi/10.1159/000506713).…”
mentioning
confidence: 99%